VD_FINDINFO Décision / 2015 / 542 vom 13. August 2015 - VD Tribunal cantonal (2015)
FICTION DE LA NOTIFICATION, DÉLAI DE RECOURS | 356 al. 2 CPP (CH), 88 al. 1 let. a CPP (CH), 88 al. 1 let. c CPP (CH)